Validation of Novel High-Performance Liquid Chromatography Method for Meropenem Quantification in Plasma - Aleksandar Rančić; Marko Folić; Nemanja Petrović; Violeta Ilić Todorović; Milica Stanojević; Miloš Milosavljević; Milica Milentijević; Slobodan Janković (Polskie Towarzystwo Farmaceutyczne, 2024)
Eminent societies of clinicians worldwide advise the implementation of therapeutic monitoring of meropenem. Our aim was to validate the new high-performance liquid chromatography (HPLC) technique for the measurement of meropenem in plasma that we developed. The validation of the method was performed in accordance with the official European Medicines Agency (EMA) guideline for bioanalytical method validation through the assessment of the following validation parameters: linearity and limit of detection/quantification, trueness and precision, recovery, selectivity, matrix-effect assessment, dilution integrity, carry-over assessment, and stability. Our calibration curve was found to be linear over the concentration ranges of 1.25-100 μg/mL, which covers the therapeutic range of meropenem in patients. From the calibration curve, the limits of detection and quantification were calculated to be 0.4 μg/mL and 1.2 μg/mL, respectively. Recovery ranged from 81.7 to 95.9 percent. Intra-day truennes ranged from −1.9 to 2.6% and inter-day trueness ranged from −4.7 to 3.8%. Intra-day precision was less than 4 percent, while inter-day precision was less than 7 percent. Meropenem remained stable in the patient plasma sample for one week at −20°C. Our HPLC technique can be applied in clinical practice for the therapeutic monitoring of meropenem in critically ill and other vulnerable patients since it is simple, rapid, and reliable.